A Rational Expectations Theory of Kinks in Financial Reporting - Guttman, Ilan; Kadan, Ohad; Kandel, Eugene (The Accounting Review, 2006)
We present a rational model of earnings management. An informed manager, whose compensation is linked to the stock price, trades off the benefit of boosting the stock price by inflating the reported earnings against the costs of such manipulation. The investors rationally interpret his actions and adjust the price accordingly. When the distribution of true earnings and the compensation scheme are smooth, the conventional equilibrium in this signaling framework is also smooth and fully revealing. In this paper, we show that in the same “smooth” environment there exist equilibria in which kinks and discontinuities emerge endogenously in the distribution of reported earnings. The manager optimally chooses a partially pooling strategy, introducing endogenous noise into his report. The resulting vagueness enables the manager to reduce the average manipulation costs. The equilibrium has perfect revelation of earnings in the right and left tails of the distribution, while for intermediate earnings realizations, we get one or more pools that manifest themselves as discontinuities in the distribution of reported earnings. We study the properties of these partially pooling equilibria and suggest applications to financial reporting.